Fabrication of Co3O4/PEI-GO composites for gas-sensing applications at room temperature. (June 2018) - Zhang, Xinci; Zhong, Hua; Xu, Laidi; Wang, Shuhong; Chi, Huanzhe; Pan, Qingjiang; Zhang, Guo
Graphical abstract: Highlights: A new controllable dispersion of Co3 O4 /PEI-GO is synthesized by hydrothermal method. The Co3 O4 /PEI-GO displays perfect sensing performance at room temperature to NOx detection. It shows lower detection limit of the thin film sensor down to 100 ppb in the air at room temperature. In Situ Diffuse Reflectance Infrared Transform Spectroscopy (DRIFT) has been made to understand the adsorption of NOx . The electronic core-shell configuration model and equivalent circuits has been establishes to explain the gas mechanism. Abstract: In this work, highly dispersed and different morphologies of Co3 O4 on the surface of GO modified with polyethylenimine (PEI) were synthesized by hydrothermal method at different temperatures. Co3 O4 /PEI-GO exhibited better gas sensing properties for NOx gas than the pure Co3 O4 and Co3 O4 /GO. Especially, the Co3 O4 /PEI-GO composite with hydrothermal at 190 °C for 3 h showed excellent sensitive characteristics to NOx at room temperature. The cause of good gas sensing property come mainly from the synergy between Co3 O4 and graphene oxide (GO) modified with PEI, which can significantly enhance the gas sensing performance. The adsorption species of NOx on the surface of Co3 O4 /PEI-GO composite sensor was detectable by In Situ Diffuse Reflectance Infrared Transform Spectroscopy (DRIFT). The electronic core-shell configuration model has been established to illustrate the resistance change when the Co3 O4 is exposed to oxidizing gases. Hence, the Co3 O4 /PEI-GO composite materials are promising in application of detecting NOx gas sensing.